Analysis of Radiation Structure of Circular Microstrip Antenna using Characteristic Mode Analysis for ISM Band - SABILA, LIYA YUSRINA; AMRI, MUHAMMAD MIFTAHUL; YUDHANA, ANTON; AKRIMA, ASRA; PRATAMA, IGO PUTRA (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2023)
ABSTRAKMakalah ini bertujuan untuk melihat karakteristik struktur radiasi menggunakan Analisis Mode Karakteristik pada antena sirkular array. Kontribusi utama dari pekerjaan ini adalah menganalisis penyebab masalah antena yang tidak sesuai dengan impedansinya pada frekuensi 2,4 GHz melalui mode distribusi arus pada patch atau radiasi. Pencocokan impedansi dapat dicapai dengan menetapkan slot ke dua patch yang tersusun dan memberikan efek peningkatan bandwidth dan gain. Untuk validasi hasil performansi antena dapat dilihat dari mode aktif pada frekuensi yang sesuai. Ditemukan bahwa antena yang diusulkan memiliki dua mode aktif pada frekuensi 2,4 GHz. Ditemukan bahwa antena yang digunakan cukup akurat. Hal ini dibuktikan dengan nilai S11 sebesar -19,606 dB dan gain sebesar 3,45 pada frekuensi 2,45 GHz.Kata kunci: antena, mikrostrip, characteristic mode analysis, ISM Band, 2.4 GHzÂ ABSTRACTThis paper aims to see the characteristics of the radiation structure using Characteristic Mode Analysis on circular array antennas. The main contribution of this work is to analyze the causes of the problem of the antenna not matching its impedance at the 2.4 GHz frequency through the current distribution modes on the patch or radiation. Matching impedance can be achieved by assigning slots to the two arrayed patches and increasing bandwidth and gain. It can be seen from the active modes at the appropriate frequency to validate the results of antenna performance. The proposed antenna has two active modes at a frequency of 2.4 GHz. It is found that the proposed antenna is entirely accurate. It is proven by the S11 value of -19.606 dB and the gain of 3.45 at a frequency of 2.45 GHz.Keywords: antenna, microstrip, characteristic mode analysis, ISM Band, 2.4 GHz